KEPATUHAN PAJAK PELAKU UMKM DENGAN MODERASI KEADILAN PAJAK SEBUAH PENDEKATAN STRUKTURAL - Hardiningsih, Pancawati; Srimindarti, Ceacilia; Sutrisno, Catur Ragil (JURNAL AKUNTANSI DAN AUDITING, 2020)
The problem of low tax compliance is an ongoing problem in the taxation field. This conditionis very ironic with the growth rate of the number of businesses in Indonesia. This study aims toempirically examine the effect of understanding tax, service quality, and tax rates on taxcompliance. This study also examines tax justice as a moderating variable. The population inthis study is the UMKM taxpayer in the city of Semarang as many as 145 MSMEs in the 6 KPPPratama areas of the city of Semarang. The sample selection technique uses conveniencesampling method and obtained 110 MSMEs. Data were analyzed using the Smart Partial LeastSquare technique. The results showed that tax understanding, service quality and tax ratesaffect taxpayer compliance. While tax justice does not moderate the tax rates on taxcompliance. This research is able to explain that awareness of taxpayers starts to grow theimportance of paying taxes, therefore the government must improve public facilities andequitable development for the benefit of the community properly and correctly throughincreasing more intensive education at MSMEs.